Proyecto de factibilidad para creación de una empresa de servicios especializada en marketing olfativo aromarketing para el mercado corporativo del norte de la ciudad de Quito - Álvaro Cornejo, Sofía Alexandra (2015)
The Olfactory Marketing is part of multi-sensory marketing, strategy invisible perceived through the senses, and that appeals to our emotions and intellect. Today consumers reach them everyday either way, hundreds of signals: images, sounds, papers, and other advertising that is never fully processed by the person because of the visual and noise pollution that exists in the field marketing and advertising. For this and other reasons have discovered the importance of developing new forms of communication, oriented novel concept of Marketing Olfactory, which seeks to offer customers an experience through the sense of smell, in order to maximize recall people and its impact on the purchase. When we perceive a pleasant scent usually breathe deeply, relax and our attitude becomes positive. The shops and outlets are the most appropriate places to promote odotype association with the brand or simply flavored with local fragrances that encourage the purchase of the products offered. It has been estimated that a point of sale flavored makes customers spend an average of 35 seconds there, increasing the likelihood of purchase. This project aims to capture a business idea to create a service company that provides marketing services to the corporate market Olfactory North of Quito, which managed to exploit the possibilities or opportunities to participate in an innovative industry.